ACCURACY ENHANCEMENT OF OMR FOR EXAM MARKING WITHOUT PRE-SET TEMPLATE USING IMAGE PROCESSING - Tow, Jingyi (IRC, 2019)
Optical Mark Recognition (OMR) is used to automate answer matching especially in the education sector. OMR marking machine is costly and limited to specific OMR paper design, thus launching researches using image processing to find less costly solutions. However, studies so far have achieved relatively low accuracy and poor consistency unless a fixed OMR form design is used. Accuracy drops with more OMR questions. Therefore, this study investigate means to improve OMR marking accuracy using enhanced algorithm designed for OMR marking. The results were compared against manual marking as the control and existing image processing algorithms. The metrics used are F1 score and percentage error for accuracy of detected answer options and marking fault respectively. The result is encouraging with consistent full accuracy for up to 90 questions as compared to previous works.